Course Continual Quality Improvement (CQI) implementation of Outcome-Based Education (OBE) in engineering education: the Kulliyyah of Engineering, IIUM experience - Ihsan, Sany Izan; Hrairi, Meftah; Khalifa, Othman Omran (2013)
Engineering education worldwide is facing new challenge in meeting the demand of industries as well as nation’s accrediting body. More countries have also begun adopting the concept of Outcome-Based Education (OBE) in their higher education teaching and learning activities, including Malaysia. In Malaysia, through the initiative of the Engineering Accreditation Council of Malaysia (EAC), all bachelor degree in engineering are required to implement OBE and have a mechanism to assess its implementation for the purpose of Continual Quality Improvement (CQI). In this paper, the experience of the Kulliyyah of Engineering of IIUM in OBE and assessment of its implementation is presented. A simple yet meaningful template has been developed in-house, to assess students’ achievement at the level of course through course learning outcome (LO) assessment, as well as program level – through program learning outcome (PO) mapping to LO. General characteristics and feature of the template will be discussed with some examples. Finally challenges in the implementation are discussed and future planning in improving the template is presented.